2003
DOI: 10.1242/jcs.00176
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear RanGTP is not required for targeting small nucleolar RNAs to the nucleolus

Abstract: The small GTPase Ran is the central regulator of macromolecular transport between the cytoplasm and the nucleus. Recent work has suggested that RanGTP also plays an important role in regulating some intra-nuclear processes. In this study, we have investigated whether RanGTP is required for the intra-nuclear transport of RNAs. Specifically, we directly analyzed the nucleolar localization of Box C/D and Box H/ACA small nucleolar RNAs (snoRNAs)in mammalian (tsBN2) cells, Saccharomyces cerevisiae and Xenopus oocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 72 publications
1
16
0
Order By: Relevance
“…Instead, we found that T. vaginalis snRNAs have unmodified 59 termini. The biological significance of a TMG 59-cap structure on snRNAs is not fully understood; however, roles in trafficking and snRNP assembly have been proposed (Huber et al 2002;Mouaikel et al 2002;Narayanan et al 2003;Cougot et al 2004). Whether the lack of a 59 cap influences trafficking and/or assembly of T. vaginalis snRNAs awaits further analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, we found that T. vaginalis snRNAs have unmodified 59 termini. The biological significance of a TMG 59-cap structure on snRNAs is not fully understood; however, roles in trafficking and snRNP assembly have been proposed (Huber et al 2002;Mouaikel et al 2002;Narayanan et al 2003;Cougot et al 2004). Whether the lack of a 59 cap influences trafficking and/or assembly of T. vaginalis snRNAs awaits further analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylation of snRNA cap structures occurs in the cytoplasm in humans and in the nucleolus in yeast. The biological significance of the distinctive 59-cap structure found in snRNAs is unclear, but it has been suggested to play roles in snRNA compartmentalization and/or transport (Huber et al 2002;Mouaikel et al 2002;Narayanan et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…mca38f3; Encor Biotechnology, Alachua, FL), Nop58 For sequential RNA and DNA fluorescence in situ hybridization, HeLa cells seeded on etched CELLocate coverslips (Eppendorf, Hamburg, Germany) were injected and fixed after 2 h in 4% formaldehyde, 10% acetic acid, and PBS for 10 min. The Cy3-labeled in situ oligonucleotide probe against human U3 snoRNA was used as previously described (Narayanan et al, 2003). The etched area of the CELLocate coverslips were imaged for U3 snoRNA, DAPIstained nuclei, and phase contrast, and then the DNA in situ hybridization was performed as stated above.…”
Section: Dna In Situ Hybridization and Immunofluorescencementioning
confidence: 99%
“…The Cy3-labeled in situ oligonucleotide probe against human U3 snoRNA was used as previously described (Narayanan et al, 2003). The etched area of the CELLocate coverslips were imaged for U3 snoRNA, DAPIstained nuclei, and phase contrast, and then the DNA in situ hybridization was performed as stated above.…”
Section: Dna In Situ Hybridization and Immunofluorescencementioning
confidence: 99%
“…Nonviral methods, including microinjection and electroporation, can also be used to deliver proteins into cells (5)(6)(7). Both antibodies (8,9) and mutant proteins (10) have been delivered into cells via microinjection. However, microinjection is limited to a relatively small number of target cells and needs specialized equipment.…”
mentioning
confidence: 99%